Visual loss in pregnancy. Issue 5 (5th May 2019) - Bachmeier, Caroline Annette Erika; Snell, Cameron; Morton, Adam
Abstract : Visual loss in pregnancy may be caused by a variety of reasons including pituitary adenomas. Prolactinomas (PRLs) are the most common hormone-secreting tumours in pregnant women. As most PRLs present with menstrual abnormalities, infertility or galactorrhoea, they are most commonly diagnosed before pregnancy. We present the case of a 30-year-old primigravida who presented at 36 +5 weeks gestation with headaches and left-sided visual loss. MRI of the pituitary gland confirmed a 10×11 mm left suprasellar mass. Results of her anterior pituitary function were unremarkable for her gestational age. Postpartum, she underwent an endoscopic endonasal resection of the pituitary tumour. The histology was consistent with a PRL. Literature review reveals only one possible case of a new diagnosis of a PRL during pregnancy. It highlights the importance to consider a wide range of differential diagnoses when assessing visual loss in pregnancy.